Internalisasi Pendidikan Karakter Dalam Mewujudkan Profil Pelajar Pancasila Di SMAN 11 Semarang - ida lutfi ayuningtyas; Pramono, Didi (Journal of Education Research, 2023)
Character education is an important aspect of Indonesian education that is being pursued by the Ministry of Education and Culture. Through the policy of strengthening the dimension of the Pancasila student profile that must be proclaimed in Indonesian educational institutions, it is considered to have an urgency towards the formation of the character of the next generation in accordance with national values and ready to face globalization in the twenty-first century era. This study aims to find out how the internalization of character education affects the profile of Pancasila students through the habituation process in SMA Negeri eleven Semarang. This study was conducted using a qualitative approach using the case study method. Research Data were collected through observation techniques, interviews, and documentation studies supported by relevant literature reviews. The results showed that SMA Negeri eleven Semarang has succeeded in internalizing character education to students through the practice of intracurricular, cocurricular, and extracurricular activities in which efforts are made to inhabit the sub-elements. Keyword:  internalization, character education, habituation, Pancasila student profile.